Biocatalysis and agricultural biotechnology - Priyadarshini, Anjali; Pandey, Prerna
This new volume, Biocatalysis and Agricultural Biotechnology: Fundamentals, Advances, and Practices for a Greener Future, looks at the application of a variety of technologies, both fundamental and advanced, that are being used for crop improvement, metabolic engineering, and the development of transgenic plants. The science of agriculture is among the oldest and most intensely studied by mankind. Human intervention has led to manipulation of plant gene structure for the use of plants for the production of bioenergy, food, textiles, among other industrial uses. A sound knowledge of enzymology as well as the various biosynthetic pathways is required to further utilize microbes as sources to provide the desired products for industrial utility. This volume provides an overview of all these aspects along with an updated review of the major plant biotechnology procedures and techniques, their impact on novel agricultural development, and crop plant improvement. Also discussed are the use of "white biotechnology" and "metabolic engineering" as prerequisites for a sustainable development. The importance of patenting of plant products, world food safety, and the role of several imminent organizations is also discussed. The volume provides an holistic view that makes it a valuable source of information for researchers of agriculture and biotechnology as well as agricultural engineers, environmental biologists, environmental engineers, and environmentalists. Short exercises at the end of the chapters help to make the book suitable for course work in agriculture biotechnology, genetics, biology, biotechnology, and plant science.